Effect of volumetric concentration of MWCNTs on the stability and thermal conductivity of nanofluids - Rehman, W.U. (American Institute of Physics Inc., 2016)
Environmental concerns and running down of the fossil fuel deposits which are generally being used as base oil in Drilling Fluid/Mud have attended worldwide attention and thereby, researchers have focused on using environmentally friendly drilling fluids. This study demonstrates the preparation of drilling fluids and to explore the effect of increase in the volumetric concentration of nanoparticles on the stability and thermal conductivity of nanofluids. In this research, for the formation of nanofluids, Jatropha Seed Oil was used as the base oil with the addition of multi-walled carbon nanotubes as the nanoparticles using sonication technique. The raw multi-walled carbon nanotubes were characterized by using SEM for morphological examination. The prepared drilling fluid were characterized by using UV-Visible spectroscopic technique for analyzing the stability. Thermal Conductivity measurements were also carried out for heat transfer efficiency. It was observed that the heat transfer capability of the nanofluid ameliorates with the increase in the loading percentage of multi-walled carbon nanotubes. Â© 2016 Author(s).